PENGEMBANGAN MEDIA POP UP BOOK PADA MATERI KEANEKARAGAMAN HAYATI KELAS V SD NEGERI 076 PALEMBANG - Azzahra, Nur; Manullang, Jujur Gunawan; Arni, Yusni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to develop valid and practical Pop Up Book learning media. The type of research used is Research and Development (R&D) with the ADDIE method consisting of analysis, design, development, implementation, evaluation. The results of the Pop Up Book learning media research were declared valid as indicated by the validation results by the validator obtaining an average percentage of 87.3% with a very valid category. Then, the results of the Pop Up Book learning media research were declared practical as seen from the assessment of educator responses obtaining an average percentage of 96% with very practical criteria, one-on-one student responses obtaining an average percentage of 88.6% with very practical criteria, and small groups obtaining an average percentage of 89.2% with very practical criteria, based on the calculation of the overall response of educators and students obtaining an average percentage of 89.92% with a very practical category. It can be concluded that the Pop Up Book learning media on the material of biodiversity for elementary school students that was developed is very valid and very practical to use as a learning medium.